PERFORMA REPRODUKSI SAPI BALI BETINA DENGAN PARITAS BERBEDA DI KECAMATAN AWANGPONE, KABUPATEN BONE, SULAWESI SELATAN - E. L. S., ALISI; IDRUS, M.; FIRMIATY, S. (Fakultas Peternakan Universitas Udayana, 2023)
The population of Bali cattle in Bone Regency on 2021 is 275,571 cattles or 19.03% of the total population in South Sulawesi. The improvement Bali cattle genetics and increasing population is carried out by the SIWAB UP- SUS government program, that is Artificial Insemination (AI). In fact the result of AI was below of 30%, therefore needed a study was conducted to determine the reproductive performance of Bali cattle on several parity. Repro- ductive performance that is Service per Conception (S/C), Conception Rate (CR), Days Open (DO), Calving Interval (CI), and Postpartum Estrus (PPE) in different parities. The results showed that for Parity 1, Parity 2, Parity 3, and Parity 4, the respective values were for S/C ratio of 1.33, 1.16, 1.23, and 1.13; CR value of 70.00%, 86.66%, 80.00%, and 86.67%; DO value of 93.73 days, 90.33 days, 93.27 days, and 88.93 days; CI value of 367.83 days, 368.00 days, 366.30 days, and 362.77 days; and EPP value of 72.16 days, 71.86 days, 72.13 days, and 68.83 days. The analysis of reproductive performance of female cattle in this region indicates normal fertility, and the best performance was Parity 4. In conclusion, the reproductive performance of Bali cattle differs for each parity in the Awangpone Subdis- trict of Bone Regency, South Sulawesi.